Attacks in Wireless Sensor Network- A Review - Kaur, Amandeep; Singh Kang, Sandeep (International Journal of Computer Sciences and Engineering, 2025)
In wireless multi-hop sensor networks, an intruder may launch some attacks due to packet dropping in order to disrupt the communication. To tolerate or mitigate such attacks, some of the schemes have been proposed. But very few can effectively and efficiently identify the intruders. The Packet Droppers and Modifiers are common attacks in wireless sensor networks. It is very difficult to identify such attacks and this attack interrupts the communication in wireless multi-hop sensor networks. Today wireless communication technique has become an essential tool in any application that requires communication between one or more sender(s) and multiple receivers. Since multiple users can use this technique simultaneously over a single channel, security has become a huge concern. Even though there are numerous ways to secure a wireless network and protect the network from numerous attacks, providing 100% security and maintaining confidentiality is a huge challenge in recent trends. This paper is all about various attacks that can affect WSN. Some attacks disturb nodes, some disturbs network, some drops packets, some theft information. Different remedies and precautions are taken to overcome different attacks.